Sex-specific associations between the triglyceride-glucose index and new-onset hypertension in a hospital employee cohort: evidence from longitudinal annual health examinations - Sun, Ruixue; Cai, Jianze; Yan, Shaorong; Qian, Jue; Fu, Cheng; Lin, Yuzhan (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index is a surrogate marker of insulin resistance and has been associated with incident hypertension. However, evidence regarding sex-specific differences in this association remains limited. This study aimed to investigate whether sex modifies the association between the TyG index and incident hypertension in the general population.MethodsWe conducted a retrospective cohort study involving 3,465 employees who underwent annual health check-ups in 2021 at the Third Affiliated Hospital of Wenzhou Medical University, with follow-up until December 2024. Participants with hypertension at baseline were excluded. The TyG index was calculated as ln [fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Cox proportional hazards models and restricted cubic spline (RCS) analyses were used to evaluate the association between TyG index and incident hypertension across sex-specific subgroups. Sensitivity analyses tested robustness.ResultsThe incidence of hypertension increased across TyG quartiles in both sexes (p < 0.01). In women, the highest TyG quartile was associated with a significantly higher hypertension risk (HR = 1.82, 95% CI: 1.06–3.13). In men, the association was attenuated after adjustment. The results of the RCS analysis revealed that when TyG levels were high, the risk of hypertension was greater in men than in women. This conclusion was partially validated by the findings from the sensitivity analyses.ConclusionsIn this retrospective cohort study based on annual health check-up data from hospital employees, we found that the TyG index may be positively associated with the risk of new-onset hypertension, with differences observed between sexes. Further research is needed to validate these findings and address potential confounding and concerns about generalizability.